Family and life insurance purchase decision-making: The significance of personal values - Oluwaseyitan, Rotimi Cephas; Hashim, Haslinda; Raja Yusof, Raja Nerina; Tee, Keng Kok (Human Resource Management Academic Research Society, 2023)
Over the decades, considerable studies have established the connection between values and their relevance to consumer behaviors. However, there needs to be more research on how values impact decision-making roles within the family. Accordingly, this paper seeks to address this apparent gap. This conceptual paper draws from the mixed review of the extant literature that revolves around the key themes of this subject. This paper emphasized the significance of values within the family setting and their potential impact on decision roles between husband and wife. The paper draws on The Theory of Basic Human Values to understand decision-making power about personal values. With this model, a four-category typology of family types is suggested in this paper and their decisive role outcomes. Traditional Valued Couple, Power Valued Couple, and Security Valued Couple. This paper has significant implications for family purchase decisions about segmentation, targeting, advertising, and personal selling. It also brings to attention how deeply ingrained values are and how they affect the dynamics of husbands' and wives’ decision-making. This paper explores the concepts of decision roles in family settings within the marketing literature vis-à-vis the role of values, which is rarely examined.